ISOLASI DAN KARAKTERISASI BAKTERI AMILOLITIK DARI SAMPEL AIR PANTAI PARIS TIGARAS - Vila Tria Putri; Rasyidah Rasyidah; Ulfayani Mayasari (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2023)
Amylolytic bacteria have great genetic diversity with high enzymatic activity and have the expertise to break down starch into simpler materials and degrade organic substances in water. This study aims to determine the variety of types of amylolytic bacteria obtained and to see how the characterization of bacteria is isolated from the waters of Paris Tigaras Beach. Isolation of amylolytic bacteria from the waters of Paris Tigaras Beach was carried out using the spread plate method taken from the last dilution of 10-5. Isolates ST3 03 and ST3 04 showed amylolytic activity by showing a clear zone of 11.8 mm in isolates ST3 03 and 8.2 mm in isolates ST3 04. Characterization of isolates ST3 03 and ST3 04 was observed including Gram-positive bacteria with rod-shaped cells, that can produce catalase enzymes, ferment three types of sugars, and move (motil). From the results of observations of the morphology of bacterial colonies and cells, and biochemical tests, isolates of amylolytic bacteria ST3 03 and ST3 04 belong to the genus Bacillus.